The Effect of Lifestyle and Financial Literacy on The Financial Management Behavior of Housewives in Banyusari Village - Dwi Prasetyo, Hendra (Lafadz Jaya Publisher, 2024)
Financial literacy is knowledge and ability to behave towards finances as an effort to improve financial management and financial decision making in order to create financial prosperity. Lifestyle can show the way someone lives their life, how someone uses their money, and how someone spends their time. In this research, researchers used a quantitative research approach. The results of this research are goodpartially or jointly, lifestyle and financial literacy have a positive and significant influence on the financial management behavior of housewives in Banyusari Village. The amount of influence is 31.9%.